Soviet bloc and the third world : Political economy of East - South relations / edited by Brigitte H. Schulz and William W. Hansen - Schulz, Brigitte H. (ed.) (London, 1989)
Only a decade ago, the foreign policy successes of the East in the Third World seemed to confirm the worst fears of many in the West about the aggressively expansionistic nature of the Soviet bloc. Now, however, the prospects for building socialism in the periphery seem much more limited. This book examines the nature of East-South relations within the context of a changing international division of labor as well as changing national economic considerations. In particular, contributors discuss the development model advocated by the East and its effectiveness in helping socialist allies in the South overcome de pendency; the response of the East, in both theory and practice, to the call for a new international economic order; the extent of competition among Soviet bloc countries in their relations with Third World countries and the relative influence of ideology and economic self-interest in structuring the East's relations with the South. Although a stimulating array of views is presented, contributors agree that economic consid erations are an increasingly important component of East-South relations, the East's political rhetoric to the contrary notwithstanding.